Ion selectivity and gating behavior of the CorA-type channel Bpss1228 - Zhu, Yibo; Wang, Yu; Zhang, Yanjing; Pu, Mengjun; Miao, Wenqian; Bai, Mingran; Bao, Rui; Geng, Jia (Frontiers in Chemistry, 2022)
Magnesium is an essential element to sustain all forms of life. Total intracellular magnesium content is determined by the balance of magnesium influx and efflux. CorA is a divalent selective channel in the metal ion transport superfamily and is the major Mg2+ uptake pathway in prokaryotes and eukaryotic mitochondria. Previous studies have demonstrated that CorA showed distinct magnesium bound closed conformation and Mg2+-free states. In addition, CorA is regulated by cytoplasmic magnesium ions and its gating mechanism has been investigated by electron paramagnetic resonance technique and molecular dynamic simulations. Here, we report a study of the putative CorA-type channel Bpss1228 from Burkholderia pseudomallei, which has been shown to be significantly associated with pseudomallei infection. We expressed and purified the Bpss1228 in full-length. Subsequently, electrophysiological experiments further investigated the electrical characteristics of Bpss1228 and revealed that it was a strictly cation-selective channel. We also proved that Bpss1228 not only possessed magnesium-mediated regulatory property a remarkable ability to be modulated by magnesium ions. Finally, we observed the three-step gating behavior of Bpss1228 on planar lipid bilayer, and further proposed a synergistic gating mechanism by which CorA family channels control intracellular magnesium homeostasis.